Inhibition of poly(ADP-ribose) polymerase interferes with Trypanosoma cruzi infection and proliferation of the parasite. - Salomé C Vilchez Larrea (Public Library of Science (PLoS), 2012)
Poly(ADP-ribosylation) is a post-translational covalent modification of proteins catalyzed by a family of enzymes termed poly(ADP-ribose) polymerases (PARPs). In the human genome, 17 different genes have been identified that encode members of the PARP superfamily. Poly (ADP-ribose) metabolism plays a role in a wide range of biological processes. In Trypanosoma cruzi, PARP enzyme appears to play a role in DNA repair mechanisms and may also be involved in controlling the different phases of cell growth. Here we describe the identification of potent inhibitors for T. cruzi PARP with a fluorescence-based activity assay. The inhibitors were also tested on T. cruzi epimastigotes, showing that they reduced ADP-ribose polymer formation in vivo. Notably, the identified inhibitors are able to reduce the growth rate of T. cruzi epimastigotes. The best inhibitor, Olaparib, is effective at nanomolar concentrations, making it an efficient chemical tool for chacterization of ADP-ribose metabolism in T. cruzi. PARP inhibition also decreases drastically the amount of amastigotes but interestingly has no effect on the amount of trypomastigotes in the cell culture. Knocking down human PARP-1 decreases both the amount of amastigotes and trypomastigotes in cell culture, indicating that the effect would be mainly due to inhibition of human PARP-1. The result suggests that the inhibition of PARP could be a potential way to interfere with T. cruzi infection.